2021
DOI: 10.3390/ma14195687
|View full text |Cite
|
Sign up to set email alerts
|

A Wind Tunnel Experimental Study of Icing on NACA0012 Aircraft Airfoil with Silicon Compounds Modified Polyurethane Coatings

Abstract: Ice formation on the aerodynamic surfaces of an aircraft is regarded as a major problem in the aerospace industry. Ice accumulation may damage parts, sensors and controllers and alter the aerodynamics of the airplane, leading to a range of undesired consequences, including flight delays, emergency landings, damaged parts and increased energy consumption. There are various approaches to reducing ice accretion, one of them being the application of icephobic coatings. In this work, commercially available polyuret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In recent years, they have garnered widespread interest due to their environmental friendliness and recyclability. They have shown significant advancements in terms of service life, durability, and safety, 3 finding applications in various fields such as automobiles, 4,5 aircraft, 6,7 construction, 8−11 and medical devices. 12−14 Usually, the self-healing supramolecular PU occurs through various interactions at the fracture site, such as hydrogen bonds (H-bonds), 15−17 ionic interactions, 18 π−π stacking, 19−21 disulfide bonds, 22−24 Diels−Alder (D-A) thermoreversible covalent bonds, 25,26 metal−ligand coordination bonds, 21 and synergistic interactions of various forces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, they have garnered widespread interest due to their environmental friendliness and recyclability. They have shown significant advancements in terms of service life, durability, and safety, 3 finding applications in various fields such as automobiles, 4,5 aircraft, 6,7 construction, 8−11 and medical devices. 12−14 Usually, the self-healing supramolecular PU occurs through various interactions at the fracture site, such as hydrogen bonds (H-bonds), 15−17 ionic interactions, 18 π−π stacking, 19−21 disulfide bonds, 22−24 Diels−Alder (D-A) thermoreversible covalent bonds, 25,26 metal−ligand coordination bonds, 21 and synergistic interactions of various forces.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, they have garnered widespread interest due to their environmental friendliness and recyclability. They have shown significant advancements in terms of service life, durability, and safety, finding applications in various fields such as automobiles, , aircraft, , construction, and medical devices. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it allows for a thorough, continuous analysis of the properties of the created polymeric materials. Our previous research has indicated the advantageous impacts of organosilicon compounds on the physicochemical and mechanical characteristics of not only polylactide, but also other types of polymers [ 47 , 48 , 49 ]. In this study, blends of PLA (polylactic acid) and silicone polymer, with varying mass content of each component, were produced using precise dosing methods.…”
Section: Introductionmentioning
confidence: 99%